Why coconut water is both a biostimulant and an anti-cancer agent - Reyes Estevez, Estefany (SLU/Dept. of Biosystems and Technology (from 130101), 2021)
Coconut water (CW) naturally contains phytohormones called cytokinins, which exist in different forms like kinetin, kinetin riboside and zeatin. The bioactive cytokinins in plants are the zeatin-type, and these natural compounds exert many vital plant physiological effects. Nutrient media based on CW is effective in augmenting nutrition efficiency, abiotic stress tolerance and crop quality in soil-cultivated, as well as in micropropagated plants. Moreover, CW is increasingly being utilized as a natural biofertilizer in crop cultivation to obtain better produce. This is because the natural cytokinins in CW increase the total available pool of cytokinins for plant growth when added to the roots. In addition to photosynthesis, cytokinins guide the appropriate development of meristems and cell cycle rates according to the growth environment, utilizing minerals as building blocks. Interestingly, these plant cytokinins also have important effects on human and other animal cells. Being rich in minerals (mainly potassium but also magnesium, calcium, and sodium), makes CW good for replenishing dehydration as well. Treatments with CW have presented other beneficial medical effects because of their specific cytokinin (kinetin and kinetin riboside) content. Targeting malignant cells and consequently acting anti-proliferatively, as well as inducing apoptosis, gives them the potential of becoming key therapeutic ingredients in treating and preventing various types of human cancers, thrombosis as well as signs of aging (cosmetics). Although, it is possible that, equivalent to plants, a conversion to zeatin-type cytokinins is required for the kinetin-type to have positive biological function in humans. This concludes that further research on the plant cytokinin-biosynthesis and metabolic pathways in humans is needed.